2017
DOI: 10.25081/jmb.2017.v1.41
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils of Juniperus phoenicea from North Western Algeria

Abstract: Juniperus phoenicea (Family: Cupressaceae) is an evergreen tree widely distributed in North Africa including Algeria. The aim of this investigation was to analyse the antimicrobial potential of essential oils from J. phoenicea on Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia, Streptococcus sp, Bacillus sp and Candida albicans using wells and discs diffusion methods. Broth dilution method was utilized to study the minimum inhibitory concentrations (MIC) and minimum bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…These components have been reported to display antimicrobial effects. 28,33,36,37 These results are in support of the observations made by Raho et al, 38 who found that the zones of inhibition of E. coli and S. aureus were 16 and 19 mm, respectively. This activity is probably due to the ability of J. phoenicea components of the EOs to complex with both the extracellular proteins and bacterial cell walls.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These components have been reported to display antimicrobial effects. 28,33,36,37 These results are in support of the observations made by Raho et al, 38 who found that the zones of inhibition of E. coli and S. aureus were 16 and 19 mm, respectively. This activity is probably due to the ability of J. phoenicea components of the EOs to complex with both the extracellular proteins and bacterial cell walls.…”
Section: Resultssupporting
confidence: 87%
“…They may also disrupt microbial membranes. 38 Similarly, Angioni et al, 39 also reported that EOs from the leaves of J. phoenicea exhibited weak activity against S. aureus and there was no activity against E. coli or P. aeruginosa. Several studies have reported that the behavior of EOs and antimicrobials can be severely modified under the presence of solvents or influence of factors such as pH, the ability of the antibacterial compound to diffuse uniformly through the agar, the volume of EO placed on the paper disks, or thickness of the agar layer.…”
Section: Resultsmentioning
confidence: 96%